2016
DOI: 10.1158/1078-0432.ccr-15-2274
|View full text |Cite
|
Sign up to set email alerts
|

Myc-Driven Glycolysis Is a Therapeutic Target in Glioblastoma

Abstract: PURPOSE Deregulated Myc drives an oncogenic metabolic state, including pseudohypoxic glycolysis, adapted for the constitutive production of biomolecular precursors to feed rapid tumor cell growth. In glioblastoma (GBM), Myc facilitates renewal of the tumor initiating cell reservoir contributing to tumor maintenance. We investigated whether targeting the Myc-driven metabolic state could be a selectively toxic therapeutic strategy for GBM. METHODS The glycolytic dependency of Myc-driven GBM was tested using 13… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
93
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 45 publications
8
93
0
Order By: Relevance
“…Gene expression and protein analyses indicated that ibrutinib (also used to treat CLL and other lymphomas) unleashes strong upregulation of Nampt which makes these cells more susceptible to NAD + -depleting agents. Overall, as recently described for IDH1 mutant and MYC-overexpressing tumor cells [14,15], our study confirms metabolic pathway as TKI sensitizer. As a result, Nampt-targeting emerges as an effective approach not only when coupled to standard chemotherapy or radiotherapy, as previously reported, but also in patients receiving more modern, molecularly targeted agents, making them more effective (Figure 1).…”
supporting
confidence: 89%
“…Gene expression and protein analyses indicated that ibrutinib (also used to treat CLL and other lymphomas) unleashes strong upregulation of Nampt which makes these cells more susceptible to NAD + -depleting agents. Overall, as recently described for IDH1 mutant and MYC-overexpressing tumor cells [14,15], our study confirms metabolic pathway as TKI sensitizer. As a result, Nampt-targeting emerges as an effective approach not only when coupled to standard chemotherapy or radiotherapy, as previously reported, but also in patients receiving more modern, molecularly targeted agents, making them more effective (Figure 1).…”
supporting
confidence: 89%
“…Targeting NNMT has proven beneficial for protection against diet-induced obesity through regulation of the SIRT1/NAMPT/NAD + pathway (64,74). Given the potential utility of NAMPT inhibitors in some gliomas, future studies may demonstrate the benefit of dual targeting of NNMT and NAMPT for glioma therapy (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…NAMPT is expressed at high levels in several different cancers and, therefore, this enzyme has been considered a potential therapeutic cancer target (5,9,27). Recent studies in glioblastoma have indicated specific genetic subgroups may be exquisitely sensitive to NAMPT inhibition (28,29). IDH1 mutation sensitizes GSCs to NAMPT inhibitors due to low ambient levels of NAD + , resulting from downregulation of nicotinic acid phosphoribosyltransferase (NAPRT1), which catalyzes an alternative NAD + salvage pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…IDH1 mutation sensitizes GSCs to NAMPT inhibitors due to low ambient levels of NAD + , resulting from downregulation of nicotinic acid phosphoribosyltransferase (NAPRT1), which catalyzes an alternative NAD + salvage pathway (29). MYC overexpression and MYC or N-MYC amplification in glioblastoma cells increase glycolytic flux and lower NAD + levels, similarly leading to increased susceptibility to NAMPT inhibitors (28). The relevance of the NAMPT-E2F2-ID pathway to these specific molecular contexts is an interesting question for future investigation.…”
Section: Discussionmentioning
confidence: 99%